Rat precision-cut intestinal slices to study P-gp activity and the potency of its inhibitors ex vivo. Issue 5 (August 2015) - Li, Ming; de Graaf, Inge A.M.; de Jager, Marina H.; Groothuis, Geny M.M.
Highlights P-gp inhibitors can be identified using Precision-Cut Intestinal Slices (PCIS). Relative potency (IC50) of P-gp inhibitors is correctly predicted in PCIS. P-gp activity in rat is higher in ileum than in duodenum, jejunum and colon. P-gp inhibition increases accumulation of Rhodamine 123 in the enterocytes of PCIS.